FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN MIOMA UTERI DI RUMAH SAKIT KOTA BENGKULU TAHUN 2012 - Erlindawati, Erlindawati (JURNAL MEDIA KESEHATAN, 2012)
The uterine myoma is the major maligna problem in the woman reproduction that causing the clinical syndrome especially bleeding, excessive menstruation, infertility, the repeatedly abortus, and pain due to the mass pressure. The problem of the research is the increasing numbers of the myoma case. The aim of the research is to reveal the relation between the uterine myoma and the age of mother, parity, menarche age, obesity, and the hormonal contraception in the hospital of Bengkulu. This research is a kind of analytical survey. The designed used in this research is case. The population is all mothers with the gynecological health problem, which is 1045 in number. The sample of the research is 106 mothers. The group case is 53 respondent with 53 respondent of group control, taken total sampling.The result of the research shows that there is relation between the mother age and the uterine myoma, the value: ρ = 0,000. The result also shows that there is no relation between the parity and uterine myoma, the value ρ = 0,643. There is norelation between the obesity and the uterine myoma, the value ρ = 0,104. Moreover, it is also known that there is relation between hormonal contraception and the uterine myoma, the value ρ = 0,05. It is suggested to the medical officer to always giving the proper counseling about the risk of uterine myoma, so the acceptor can choose the most feaseable and the most suitable contraception for her. It is also suggested to the women in the fertilize age to be aware of the risk of uterine myoma. It is can be by doing the advanced medical check up to the abnormal menstruation cycle syndrome.